Compressive Strength of Asphalt Concrete Binder Course (AC-BC) Mixture Using Buton Granular Asphalt (BGA). (2015) - Gaus, Abdul; Tjaronge M.W.,; Ali, Nur; Djamaluddin, Rudy
Abstract: This study aims to evaluate the compressive stress-strain relationship of asphalt concrete mixtures using Buton granular asphalt (BGA) as partial replacement for petroleum asphalt in asphalt concrete bearing course (AC-BC) mixture production. The experimental tests show that the stress-vertical strains curve and stress-horizontal strains curve pattern were similar for all mixtures. The application of BGA as partially replaced petroleum asphalt in the AC-BC mixture improved the compressive strength and elastic modulus in comparison to AC-BC mixture without BGA. No significant difference in the Poisson ratio for all mixtures was observed.